Mampukah Work Engagement Memoderasi Pengaruh Organizational Climate terhadap Burnout Syndrome pada Karyawan Perusahaan Jasa Kepelabuhan? - Wardani, Agustin Ayu; Agus Frianto (Jurnal Ilmu Manajemen, 2024)
This research will discuss organisational climate, burnout syndrome, and work engagement. This research aims to test and analyse the influence of organisational climate on employee burnout syndrome with work engagement as a moderating variable at PT. Indonesian Harbor (Persero) Regional 3 Surabaya. This research uses quantitative research. The sampling technique uses non-probability sampling with a saturated sample type, where all population members are sampled with a sample size of 94 respondents. The statistical analysis used in this research is the Structural Equation Model-Partial Least Square (SEM-PLS) with the help of SmartPLS 3.0 software. The steps taken to obtain research results are tabulating the questionnaire results, designing a measurement model (outer model), and designing a structural model (inner model). The results of this study explain that organisational climate cannot significantly influence burnout syndrome; work engagement has a significant negative effect on burnout syndrome, and work engagement succeeds in moderating the relationship between organisational climate and employee burnout syndrome.